The implementation of green practices to green consumer behavior in Food & Beverage Department at The ONE Legian - Anak Agung Putu Parwati; Luh Linna Sagitarini; I Nyoman Rajin Aryana (Journal of Applied Sciences in Travel and Hospitality, 2022)
This study aimed to determine the application of green practice and the effect of green practice on green consumer behavior in the food & beverage department at The ONE Legian, either partially or simultaneously. The population of this study is guests who stay at The ONE Legian. Data collection techniques in this study were through observation and questionnaires, where data collection was carried out by field observations, and questionnaires with fifty-five respondents. The analysis used in this study is multiple linear regression quantitative analysis using the SPSS 25 program. The results of this study indicate a positive and partially significant effect of green practices on green consumer behavior and a simultaneous positive effect of green practice variables on green consumer behavior variables. The results of the coefficient of determination test indicate that the variation of the independent variable is only able to explain fifty-three point  four percent of the dependent variable, the remaining forty-six point six is influenced by other factors outside of this study. Before the researcher conducted the research, it was found that there were problems that occurred in the food & beverage department, such as when taking food at a restaurant, many guests asked for plastic bags to wrap the food they brought. And some guests complained to the staff because plastic bags were not provided. In addition, researchers saw several guests smoking carelessly in the restaurant area which caused air pollution. This shows that there are so many guests who did not understand the implementation of green practice implemented by The ONE Legian. After implementing the green practice in the hotel, the researcher did the second observation, the results showed that there was a changed habit in guests who stayed a few days at The ONE Legian, namely guests who already know the implementation of green practice is now smoking in the smoking area that has been provided. The researcher suggests that the implementation of green donation in the food & beverage department is more published to guests or consumers. So that guests or consumers can participate and feel the green donation activity. This activity can be a motivation and example for other hotels to participate in efforts to protect the environment, both hotels around Legian and Kuta.